KOMUNIKASI NON VERBAL PADA POLA INTERAKSI BERKEBUTUHAN KHUSUS TUNAGANDA DI MASYARAKAT - Ogy Mahendra; Kemal Pri Hutama; Venny Sevtiany; Ferry Darmawan (ArtComm, 2020)
This study aims to find out how to communicate a person with a hearing impairment (deaf and deaf) in the Memen figure. The communication made by Memen is the exchange of meanings and symbols so that they affect behavior change. You can communicate and do your daily activities well, despite the limitations you have. Memen can grasp the meaning of a symbol well by his mind. With the confidence that Memen has, Memen is also supported by the surrounding environment that influences the current character of Memen. This research uses qualitative research methods with case studies. Collection techniques used through interviews, observations and literature studies and theories used are symbolic interaction theories according to George Herbert Mead which will explain the Mind, Self and Society. The results of the study, Memen did not understand nonverbal languages officially, and he understood self-taught and assisted by residents in the surrounding environment.